Contribuição da cobertura morta de longo e curto prazo para melhoria do solo, absorção de nitrogênio e produtividade do milho - Pires, Jéssica de Freitas Nunes (2020)
The dynamics and long-term responses to mulching management processes in tropical agroecosystems remain poorly understood. This study aims to evaluate the short-and long-term effects of mulching on SOM accumulation, SBC retention, and physical improvement of a cohesive tropical soil enriched with calcium. We also assess the contribution of mulching and synthetic N (Ns) to the uptake of N and maize grain yield. This experiment was conducted using a randomized block design with the following treatments: Long-term mulching (LTM), long term mulching plus nitrogen (LTM+N), short-term mulching (STM), short-term mulching plus nitrogen (STM+N), long-term mulching plus short-term mulching (LTM+STM), long-term mulching plus short-term mulching plus nitrogen (LTM+STM+N), planting with nitrogen (N), and a control. Mulch consisting of dry biomass (branches and leaves) of Gliricidia sepium applied at a rate of 12 Mg ha-1 in soil enriched with calcium. The interaction between Ns and calcium (Ca) was more intense in LTM areas, resulting in higher carbon content, base cations, enhanced soil rootability, and increased nitrogen uptake. STM maintained soil moisture, decreasing penetration resistance, and, when paired with LTM, providing enough biological nitrogen to replace Ns. The effects of STM and LTM on their own were cumulative, with Nuptake 54% higher, accumulated N 163% higher, and maize grain yield 125% higher (4.77 to 10.78 Mg ha-1). The continuous use of mulch, therefore, has benefits for both the sustainability and feasibility of tropical agro-ecosystems, preventing land degradation and avoiding deforestation.